ANALISIS JARAK SHOOTING PADA PERTANDINGAN FINAL FUTSAL PUTRA PON XXI ACEH-SUMUT 2024 - Fadilah, Arif; Raharja, Andri Tria (Journal of Physical Activity and Sports (JPAS), 2025)
The purpose of this study was to analyze the shooting distance in the men's futsal final of the 2024 Aceh-North Sumatra National Sports Week. This study used a quantitative descriptive research method with a cross-sectional design. Match videos from the Local Futbal YouTube channel were downloaded and analyzed. Shooting motion videos were cut using Movie Maker software. Then, the distance of the cut video was analyzed using Kinovea software 2023.1.2. All shooting techniques performed by 24 futsal athletes were then calculated in meters. The analysis time was carried out until the match was over or 20 x 2 minutes (net time) with 5 x 2 minutes of additional time. Data analysis was carried out based on the total shooting distance, the direction of the kick to the goal, shots on target, and shots off target. All statistical procedures were carried out using SPSS and Microsoft Excel. The results of the study showed that in the final match of the men's futsal category of PON XXI Aceh-Sumut 2024, a total of 66 shots were taken with an average shooting distance of 8.92 meters, the furthest distance of 17.76 meters, the closest distance of 1.36 meters and the percentage of shots on target was 30.3% and off target was 69.7%.